Calcitonin gene-related peptide inhibits autophagic-lysosomal proteolysis through cAMP/PKA signaling in rat skeletal muscles. (March 2016) - Machado, Juliano; Manfredi, Leandro H.; Silveira, Wilian A.; Gonçalves, Dawit A.P.; Lustrino, Danilo; Zanon, Neusa M.; Kettelhut, Isis C.; Navegantes, Luiz C.
Abstract: Calcitonin gene-related peptide (CGRP) is a neuropeptide released by motor neuron in skeletal muscle and modulates the neuromuscular transmission by induction of synthesis and insertion of acetylcholine receptor on postsynaptic muscle membrane; however, its role in skeletal muscle protein metabolism remains unclear. We examined the in vitro and in vivo effects of CGRP on protein breakdown and signaling pathways in control skeletal muscles and muscles following denervation (DEN) in rats. In isolated muscles, CGRP (10 −10 to 10 −6 M) reduced basal and DEN-induced activation of overall proteolysis in a concentration-dependent manner. The in vitro anti-proteolytic effect of CGRP was completely abolished by CGRP8-37, a CGRP receptor antagonist. CGRP down-regulated the lysosomal proteolysis, the mRNA levels of LC3b, Gabarapl1 and cathepsin L and the protein content of LC3-II in control and denervated muscles. In parallel, CGRP elevated cAMP levels, stimulated PKA/CREB signaling and increased Foxo1 phosphorylation in both conditions. In denervated muscles and starved C2C12 cells, Rp-8-Br-cAMPs or PKI, two PKA inhibitors, completely abolished the inhibitory effect of CGRP on Foxo1, 3 and 4 and LC3 lipidation. A single injection of CGRP (100 μg kg −1 ) in denervated rats increased the phosphorylation levels of CREB and Akt, inhibited Foxo transcriptional activity, the LC3 lipidation as well as the mRNA levels of LC3b and cathepsin L, two bona fide targets of Foxo. This study shows for the first time that CGRP exerts a direct inhibitory action on autophagic-lysosomal proteolysis in control and denervated skeletal muscle by recruiting cAMP/PKA signaling, effects that are related to inhibition of Foxo activity and LC3 lipidation.